A systematic review of in utero cannabis exposure and risk for structural birth defects - Sujan, Ayesha C.; Pal, Anish; Avalos, Lyndsay A.; Young-Wolff, Kelly C. (Frontiers in Pediatrics, 2023)
Cannabis use among pregnant women has increased over time. Therefore, there is a great public health need to understand the consequences of in utero cannabis exposure. While several meta-analyses and reviews have summarized the evidence of in utero cannabis exposure on adverse obstetric outcomes (e.g., low birth weight and preterm birth) and long-term offspring development, there has not been a focus on in utero cannabis exposure and risk for structural birth defects. Therefore, we conducted a systematic review using PRISMA guidelines to evaluate the association between in utero cannabis exposure and structural birth defects. We identified 20 articles to include in our review and focused on interpreting findings from the 12 that adjusted for potential confounders. We report findings by seven organ systems. Within the 12 articles, four reported on cardiac malformations, three reported on central nervous system malformations, one reported on eye malformations, three reported on gastrointestinal malformations, one reported on genitourinary malformations, one reported on musculoskeletal malformations, and two reported on orofacial malformations. Findings on associations between in utero cannabis exposure and birth defects reported in more than two articles were mixed (i.e., findings for cardiac, gastrointestinal, central nervous system malformations). Findings for associations between in utero cannabis exposure and birth defects reported in two articles (i.e., orofacial malformations) or in a single article (eye, genitourinary, and musculoskeletal) suggested that cannabis exposure was not associated with these types of malformations, but strong conclusions cannot be drawn from such sparce research. We review the limitations and gaps in the existing literature and call for more research to rigorously evaluate associations between in utero cannabis exposure and structural birth defects.